(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
One of the main subjects of linguistics nowadays is definitely code-switching. But for a variety of reasons, the interest in researching bilingualism by means of linguistic feature comparison in speech has not always been clearly visible. Originally undertaken under the structuralist paradigm, the first studies laying the foundation for the research of code-switching. Language contact was seen in this paradigm as a conflict between language and speech: bilingualism was studied from the viewpoint of the interplay of two language systems, while the living embodiment of language in speech activity did not get due attention. Structuralism regards language and its grammar as a self-sufficient, sophisticatedly structured system of interrelated elements. In this sense, code-switching is understood as the outcome of interference processes, therefore upsetting the structural integrity of this system.